2022
DOI: 10.1039/d2mo00132b
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the transcriptome and metabolome of pancreatic spheroids derived from human induced pluripotent stem cells and matured in an organ-on-a-chip

Abstract: Functional differentiation of pancreatic like tissue from human induced pluripotent stem cells is one of the emerging strategies to achieve in vitro pancreas model. Here, we propose a protocol to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…In our previous work, we have proposed a protocol to generate C-peptide and insulin secreting β-like cells in spheroids derived from hiPSCs. 16,17 We noticed that our spheroids contained also cells positive to glucagon. A bulk transcriptomic investigation revealed that the spheroids co-expressed mRNA related to several hormones’ activities (such as IAPP, INS, INHBB, GCG, 17 and SST 16 ) when compared to the control of undifferentiated cells.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…In our previous work, we have proposed a protocol to generate C-peptide and insulin secreting β-like cells in spheroids derived from hiPSCs. 16,17 We noticed that our spheroids contained also cells positive to glucagon. A bulk transcriptomic investigation revealed that the spheroids co-expressed mRNA related to several hormones’ activities (such as IAPP, INS, INHBB, GCG, 17 and SST 16 ) when compared to the control of undifferentiated cells.…”
Section: Introductionmentioning
confidence: 81%
“…16,17 We noticed that our spheroids contained also cells positive to glucagon. A bulk transcriptomic investigation revealed that the spheroids co-expressed mRNA related to several hormones’ activities (such as IAPP, INS, INHBB, GCG, 17 and SST 16 ) when compared to the control of undifferentiated cells. Those results illustrated a potential cell heterogeneity.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation